Revisiting the role of the insula and smoking cue-reactivity in relapse: A replication and extension of neuroimaging findings. (1st October 2017) - Janes, A.C.; Gilman, J.M.; Radoman, M.; Pachas, G.; Fava, M.; Evins, A.E.
Highlights: Relapse-vulnerable smokers have greater insula reactivity to smoking cues prior to cessation. Dorsal striatal smoking cue reactivity also predicted relapse vulnerability. The current findings overlap with our prior work providing much needed replication. Abstract: Introduction: The ability to direct smoking cessation treatment based on neuroscientific findings holds incredible promise. However, there is a strong need for consistency across studies to confirm neurobiological targets. While our prior work implicated enhanced insula reactivity to smoking cues in tobacco smoking relapse vulnerability, this finding has not been confirmed. Method: Using functional magnetic resonance imaging (fMRI), we evaluated the pre-cessation brain reactivity to smoking vs. neutral cues in nicotine dependent smokers who were and were not able to maintain subsequent abstinence. Results: Of the 23 (7 women) individuals assessed, 13 relapsed and there were no demographic differences between those who did and did not relapse. However, smokers who relapsed showed enhanced reactivity to smoking cues in the right insula and dorsal striatum, showing significant overlap between our current and prior work despite methodological differences, including the fact that our previous work only included women. Conclusion: The current work supports our prior results and builds on the concept that the insula and dorsal striatum work in concert to maintain nicotine dependence. Specifically, dorsal striatal-mediated habitual responding may be triggered both by the external drug-associated cues, and the insula-mediated internal states that provide additional context motivating drug use. This replicated finding also mirrors preclinical work that finds the same individualized distinction, as only some rodents attribute incentive salience to drug cues and are more likely to reinstate drug seeking after extinction. To effectively treat addiction, these individual characteristics and their underlying neurobiological foundations must be considered.